Effect of herbicide Prechlor on the performance of T. aman rice (Journal of the Bangladesh Agricultural University, 2014)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University (BAU), Mymensingh during the period from July to December 2012 to find out the effect of herbicide Prechlor 500 EC on weed control and performance of transplant aman rice. The experiment was laid out in a randomized complete block design with four replications. The experiment consisted of two varieties viz., BRRI dhan41 and Nizershail, and four levels of Prechlor @ 0, 0.5, 1.0 and 1.5 L ha-1. Monochoria vaginalis, Nymphaea nouchali, Paspalum scrobiculatum, Echinochloa crusgalli and Scirpus juncodies were the major weeds in the experimental plots. Prechlor 500EC @ 1.5 L ha-1 showed the best performance in reducing weed density, weed dry weight and increased weed control efficiency but reduce grain yield. Variety had significant influence on all the yield and yield contributing characters of rice. Higher grain yield (3.09 t ha-1) was obtained from BRRI dhan41. Different levels of Prechlor also had significant effect on yield and yield contributing characters such as number of total tillers hill-1, number of effective tillers hill-1, panicle length, spikelets panicle-1, grains panicle-1, grain yield, straw yield and harvest index. Prechlor @ 1.5 L ha-1 showed best performance with respect to most yield attributes, grain and straw yields and the lowest grain yield was obtained from Prechlor @ 0 L ha-1. The interaction effects of variety and herbicide Prechlor had significant effect on all yield attributes except plant height, effective tillers hill-1, panicle length, 1000-grain weight and harvest index. The highest grain yield (3.62 t ha-1) was obtained from variety BRRI dhan41 with Prechlor @ 1.5 L ha-1. The results suggest that farmers can be advised to use herbicide Prechlor @ 1.5 L ha-1 to boost up the production of BRRI dhan41 controlling weeds during aman season under the agro-climatic condition of the study area. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19923 J. Bangladesh Agril. Univ. 11(2): 257-264, 2013